Increased expression of bcl11b leads to chemoresistance accompanied by G1 accumulation. - Piotr Grabarczyk (Public Library of Science (PLoS), 2010)
Background The expression of BCL11B was reported in T-cells, neurons and keratinocytes. Aberrations of BCL11B locus leading to abnormal gene transcription were identified in human hematological disorders and corresponding animal models. Recently, the elevated levels of Bcl11b protein have been described in a subset of squameous cell carcinoma cases. Despite the rapidly accumulating knowledge concerning Bcl11b biology, the contribution of this protein to normal or transformed cell homeostasis remains open. Methodology/principal findings Here, by employing an overexpression strategy we revealed formerly unidentified features of Bcl11b. Two different T-cell lines were forced to express BCL11B at levels similar to those observed in primary T-cell leukemias. This resulted in markedly increased resistance to radiomimetic drugs while no influence on death-receptor apoptotic pathway was observed. Apoptosis resistance triggered by BCL11B overexpression was accompanied by a cell cycle delay caused by accumulation of cells at G1. This cell cycle restriction was associated with upregulation of CDKN1C (p57) and CDKN2C (p18) cyclin dependent kinase inhibitors. Moreover, p27 and p130 proteins accumulated and the SKP2 gene encoding a protein of the ubiquitin-binding complex responsible for their degradation was repressed. Furthermore, the expression of the MYCN oncogene was silenced which resulted in significant depletion of the protein in cells expressing high BCL11B levels. Both cell cycle restriction and resistance to DNA-damage-induced apoptosis coincided and required the histone deacetylase binding N-terminal domain of Bcl11b. The sensitivity to genotoxic stress could be restored by the histone deacetylase inhibitor trichostatine A. Conclusions The data presented here suggest a potential role of BCL11B in tumor survival and encourage developing Bcl11b-inhibitory approaches as a potential tool to specifically target chemoresistant tumor cells.